Efficacy and safety of immunotherapy in locally advanced or metastatic pulmonary lymphoepithelioma-like carcinoma: a multicenter retrospective study - Xiongwen Yang; Yi Xiao; Yubin Zhou; Hao Hu; Huiyin Deng; Jian Huang; Maoli Liang; Zihao Yuan; Longyan Dong; Shaohong Huang (Therapeutic Advances in Medical Oncology)
Background: Pulmonary lymphoepithelioma-like carcinoma (pLELC) is a rare subtype of non-small-cell lung cancer that predominantly affects younger, non-smoking individuals in southern and southeast Asia, where Epstein–Barr virus (EBV) prevalence is high. The efficacy and safety of immunotherapy in pLELC, especially in second-line settings, remain inadequately explored. Objectives: This study aimed to evaluate the efficacy of immunotherapy, either alone or in combination with chemotherapy, in improving progression-free survival (PFS) and overall survival (OS) in patients with advanced pLELC. Design: This was a multicenter retrospective study. Methods: A retrospective analysis was conducted on 252 patients with stage IIIB–IV pLELC treated across six centers. Patients received chemotherapy, immunotherapy, or a combination of both (chemoimmunotherapy). The primary outcomes measured were PFS and OS across different treatment regimens. Results: Chemoimmunotherapy significantly improved both PFS and OS compared to chemotherapy alone, in both first- and second-line settings. In first-line treatment, chemoimmunotherapy resulted in a median PFS of 17.6 months and OS of 26.1 months, compared to chemotherapy alone (PFS 8.7 months, OS 19.2 months). In the second-line setting, chemoimmunotherapy achieved a median PFS of 5.1 months and OS of 13.5 months, surpassing the outcomes with chemotherapy alone (PFS 3.3 months, OS 8.9 months). High baseline EBV-DNA levels (>2000 copies/mL) and low programmed death ligand 1 (PD-L1) expression (<50%) were associated with poorer outcomes. In addition, patients with high baseline serum tumor markers (STMs) and a dynamic reduction of ⩽20% in STMs exhibited significantly worse PFS and OS. Conclusion: The study suggests that immunotherapy, particularly when combined with chemotherapy, offers significant survival benefits for patients with advanced pLELC. Baseline EBV-DNA levels, PD-L1 expression, and both baseline and dynamic STM changes serve as important predictors of treatment response, highlighting the need for personalized therapeutic approaches in this unique subtype of lung cancer.